Neue orale Antikoagulanzien zur Prophylaxe von Schlaganfällen: Ergebnis einer Expertenkonferenz zum praktischen Einsatz bei geriatrischen Patienten = New oral anticoagulants for prophylaxis of stroke : results of an expert conference on practical use in geriatric patients - Bahrmann, Philipp; Wehling, Martin (Zeitschrift für Gerontologie und Geriatrie, 2016)
Geriatric patients with non-valvular atrial fibrillation (AF) are increasingly being treated with novel oral anticoagulants (NOAC) to prevent ischemic stroke. This article highlights the outcome of an expert meeting on the practical use of NOAC in elderly patients. An interdisciplinary group of experts discussed the current situation of stroke prevention in geriatric patients and its practical management in daily clinical practice. The topic was examined through focused impulse presentations and critical analyses as the basis for the expert consensus. The key issues are summarized in this paper. The European Society of Cardiology (ESC) guidelines from 2012 for the management of patients with non-valvular AF recommend NOAC as the preferred treatment and vitamin K antagonists (VKA) only as an alternative option. Currently, the NOAC factor Xa inhibitors apixaban and rivaroxaban and the thrombin inhibitor dabigatran are more commonly used in clinical practice for patients with AF. Although these drugs have many similarities and are often grouped together it is important to recognize that the pharmacology and dose regimes differ between compounds. Especially n elderly patients NOAC drugs have some advantages compared to VKA, e.g. less drug-drug interactions with concomitant medication and a more favorable risk-benefit ratio mostly driven by the reduction of bleeding. Treatment of anticoagulation in geriatric patients requires weighing the serious risk of stroke against an equally high risk of major bleeding and pharmacoeconomic considerations. Geriatric patients in particular have the greatest benefit from NOAC, which can also be administered in cases of reduced renal function. Regular control of the indications is indispensable, as also for all other medications of the patient. The use of NOAC should certainly not be withheld from geriatric patients who have a clear need for oral anticoagulation.
Gesehen am 29.03.2019